MEK inhibition prevents human skin graft rejection by promoting CD8+TCF1+ over CD8 effector T cells - Christine Chauveau; Veronique Nerriere-Daguin; Maeva Fourny; Cynthia Fourgeux; Thibaut Larcher; Laurence Delbos; Martin Braud; Lucas Brusselle; Olivia Rousseau; Jeremie Poschmann; Julien Verdier; Fabienne Haspot; et al. (iScience)
Summary: Pharmacological MEK inhibition might be an innovative approach to complete the immunosuppressive regimen that enables solid organ transplantation. While MEK inhibitors like trametinib are approved in oncology, their immunomodulatory properties remain poorly investigated in the context of organ transplantation, especially in human context. Using a human skin transplantation model in NSG mice reconstituted with third-party human PBMCs, we evaluated the effects of trametinib on graft survival and the human allogeneic immune response. MEK inhibition significantly prolonged graft survival without reducing graft infiltrate, while preserving the human epidermal tissue. Single-cell RNA sequencing of splenic cells revealed that MEK inhibition impaired CD8+ T cell differentiation into effector phenotypes, favoring an accumulation of CD8+ TCF1+ stem-like cells. Additionally, MEK inhibition supported CD4+ T cell homeostasis by maintaining IL-7R expression. These findings suggest that MEK inhibition may simultaneously control the alloimmune response and support immune recovery, highlighting its potential in solid organ transplantation.